Multicenter retrospective study to evaluate the impact of trabectedin plus pegylated liposomal doxorubicin on the subsequent treatment in women with recurrent, platinum-sensitive ovarian cancer. Issue 6 (July 2019) - Romero, Ignacio; Mallol, Pedro; Santaballa, Ana; Del Campo, Jose M.; Mori, Marta; González-Santiago, Santiago; Casado, Antonio; Vicente, David; Ortega, Eugenia; Herrero, Ana; Guerra, Eva; Barretina-Ginesta, Pilar; et al.
Abstract : Debulking surgery, followed by taxane/platinum-based chemotherapy has traditionally been the first-line treatment for advanced ovarian cancer. However, most patients will experience recurrence afterwards, and receive subsequent lines of therapy. It has been proposed that extending the treatment-free interval of platinum can improve the response to a subsequent platinum-based chemotherapy, and reduce associated toxicities in women with recurrent, platinum-sensitive ovarian cancer. The aim was to determine the impact, in clinical practice, of trabectedin with pegylated liposomal doxorubicin (trabectedin/PLD) on the subsequent platinum-based therapy in these patients, and to explore the prognosis for breast cancer gene status and the expression of diverse genes. This was a multicenter, retrospective, postauthorization study that involved 79 patients. Germline or somatic mutations of breast cancer gene 1/2 were present in 21.5%. The median time between trabectedin/PLD and the onset of the subsequent treatment was 6.7 months. The overall response rate during the trabectedin/PLD period was 36.7%. In the subsequent first-line platinum-based therapy, the overall response rate was 51.4%. Progression-free survival and overall survival were 11.8 and 25.4 months, respectively, from the onset of trabectedin/PLD treatment. Partially platinum-sensitive (between 6 and 12 months) and platinum-sensitive patients (treatment-free interval of platinum≥12 months) showed no differences in progression-free survival and overall survival. Grade 3 neutropenia and asthenia were reported in 15.2 and 10.1% of patients, respectively. Most frequent adverse events in more than 10% of patients were neutropenia (45.6%), asthenia (43.0%), nausea (25.3%), and anemia (13.9%). The intercalation with a nonplatinum regimen may improve the response to a subsequent platinum-based therapy in women with recurrent, platinum-sensitive ovarian cancer.